214k views
4 votes
Solve the following polynomial equation by grouping and factoring.9y3−16y=0

1 Answer

4 votes

Solve:


9y^3-16y=0

Factoring out y:


y(9y^2-16)=0

The expression in parentheses can be factored by using the special product:


a^2-b^2=(a-b)(a+b)

Therefore, the equation becomes:


y(3y-4)(3y+4)=0

Now equate each factor to 0 and solve for y:


\begin{gathered} y=0 \\ \\ 3y-4=0\therefore y=(4)/(3) \\ \\ 3y+4=0\therefore y=-(4)/(3) \end{gathered}

We have 3 solutions:

y = 0, y = 4/3, y = -4/3

User Anton Babenko
by
5.0k points